Flying Under the Radar: How Susceptible Are University Students to County Lines Victimization? - Burt, Ashley Marie (International journal of offender therapy and comparative criminology, 2024)
We quantitatively investigated how susceptible university students are to engaging in activity that could lead to County Lines involvement by asking them to rate their willingness to participate in five hypothetical scenarios typical of County Lines engagement and one control scenario (bit-coin scam). About 62% of the 116 students were willing to engage compared to only 3% in the control scenario. Participant demographics, drug abuse, mental health, financial distress, and materialism were also measured and significantly predicted willingness to engage with the scenarios with weak to moderate effect. Findings suggest that university students are vulnerable to engaging in County Lines but the risk factors in the literature may not be good predictors of determining vulnerability.